Heart rate recovery improvement in patients following acute myocardial infarction: exercise training, -blocker therapy or both - Medeiros, Wladimir Musetti [UNIFESP] (2018)
Heart rate recovery (HRR) is a strong mortality predictor. Exercise training (ET) and -blocker therapy have significant impact on the HRR of patients following myocardial infarction (MI). However, the combination of ET and -blocker therapy, as well as its effectiveness in patients with a more compromised HRR (12bpm), has been under-studied. Male patients (n=64) post-MI were divided: Training+-blocker (n=19), Training (n=15), -blocker (n=11) and Control (n=19). Participants performed an ergometric test before and after 3months of intervention. HRR was obtained during 5min of recovery and corrected by the cardiac reserve (HRRcorrCR). Compared to pre-intervention, HRRcorrCR was significantly increased during the 1st and 2nd minutes of recovery in the Training+-blocker group (705% and 375%, respectively